Role of biochar as support material for photo catalytic operation: A review - Pooja Dhiman; Manisha Dhiman; Arush Sharma; Manita Thakur; Sourav Gautam; Ajay Kumar (Sustainable Chemistry for the Environment)
Compared to the previous decades, presently the generation of household and industrial waste has increased too many folds. The resulting waste has posed a serious management problem. Various techniques are being explored for organic waste management such as biodegradation, microbial degradation, etc. But still, the processes required technological updates to minimize issues related to cost, ease of implementation, etc. Recently, the pyrolysis of such waste in the limited presence of oxygen is in trend. The product so obtained called as “Biochar” offer immense utilization in the domain of environmental pollutants remediation. Biochar offered varieties of beneficial properties, including high rough, porous as well as high specific surfaces area enriched with various active functionalities. These properties are very beneficial while being utilized as a support material in the Nano regime. The present article consolidates the broad area deployment of biochar in diversified fields including adsorption, photo catalysis etc. A special intention has been given to the deployment of biochar in the field of effluent remediation.